A Single Institutions First 100 Patients Undergoing Laparoscopic Anti-Reflux Fundoplications: Where are They 20 Years Later?. Issue 8 (August 2015) - Sadowitz, Benjamin D.; Luberice, Kenneth; Bowman, Ty A.; Viso, Alexandra M.; Ayala, Daniel E.; Ross, Sharona B.; Rosemurgy, Alexander S.
Although anti-reflux surgery has been used liberally over the past decades for the treatment of gastroesophageal reflux disease (GERD), few studies report follow-up after 10 years. This study was undertaken to report follow-up on 100 consecutive GERD patients up to 22 years after utilizing a laparoscopic fundoplication. Hundred consecutive patients undergoing laparoscopic fundoplication for GERD were prospectively followed beginning in 1992. The frequency and severity of symptoms before and after laparoscopic fundoplication were scored on a Likert scale (1 = never/none to 10 = always/very bothersome). Median data are reported. Of the 100 patients who underwent laparoscopic fundoplication for their GERD, nine were reoperations. Twenty-six patients are deceased on average 11 years after their fundoplications. Seventy-four patients are alive, with 27 patients, actively followed for 19 years after their fundoplications. At most recent follow-up, patients experienced long-term amelioration of symptom frequency and severity after fundoplication (e.g., heartburn frequency = 8–2, severity = 8–1; P < 0.01 for each). Eighty-four per cent of patients rated their symptom frequency as less than once per month. Eighty-eight per cent of patients were satisfied with their postoperative results, and 95 per cent of patients confirmed they would have the operation again knowing what they know now. Long-term follow-up documents high patient satisfaction and durable symptomatic relief up to two decades after laparoscopic fundoplication for GERD. Patients should seek this operation not only for symptomatic relief, but to mitigate the deleterious effects of long-term acid exposure and anti-acid therapy.